2015
DOI: 10.1039/c5dt00908a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent benzene-centered mono-, bis- and tris-triazapentadiene–boron complexes

Abstract: A series of novel benzene centered mono-, bis-and tris-1,3,5-triazapentadiene ligands 6a-e was synthesized and investigated with respect to their reactivity towards triphenylborane. The resulting blue-fluorescent boron complexes 14a-e with a six-membered ring chelate structure show excellent thermal and chemical stability. All title compounds were completely characterized including X-ray diffraction studies for 14a-c and 14e. Whereas the absorption spectra of all three classes of compounds are similar, the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Unlike other rigid 3-fold symmetric polycyclic aromatic hydrocarbons (PAHs), the emission profiles of compounds 6a and 6b are not the mirror image of their absorption profiles, manifesting their deformed structures in the excited states . Moreover, compounds 6a and 6b exhibit large Stokes shifts of 106 and 157 nm, respectively, which are among the highest values of the B,N-containing chromophores . Such results are reasonably attributed to the asymmetric structures of these molecules associated with their deformed discotic main backbones as the consequence of the congested circumstances, which is consistent with their single crystal structure analyses.…”
mentioning
confidence: 66%
“…Unlike other rigid 3-fold symmetric polycyclic aromatic hydrocarbons (PAHs), the emission profiles of compounds 6a and 6b are not the mirror image of their absorption profiles, manifesting their deformed structures in the excited states . Moreover, compounds 6a and 6b exhibit large Stokes shifts of 106 and 157 nm, respectively, which are among the highest values of the B,N-containing chromophores . Such results are reasonably attributed to the asymmetric structures of these molecules associated with their deformed discotic main backbones as the consequence of the congested circumstances, which is consistent with their single crystal structure analyses.…”
mentioning
confidence: 66%
“…Organoboron complexes often show brighte mission and some of them presentl uminescent chromism toward various externals timuli, including mechanical forces. [34][35][36][37][38][39][40][41][42] However,i n most cases,l uminescent chromism is cancelled out by heating. In previous studies, it was shown that POSS derivatives could suppress molecular motionso fs urroundingm olecules through covalentornoncovalent bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Organoboron complexes often show bright emission and some of them present luminescent chromism toward various external stimuli, including mechanical forces . However, in most cases, luminescent chromism is cancelled out by heating.…”
Section: Resultsmentioning
confidence: 99%
“…Although most conventional organic luminescent dyes show weak emission in the solid state due to aggregation‐caused quenching (ACQ), several strategies for overcoming this problem have been established. For example, brightly luminescent materials have been invented on the basis of the strategy for introducing bulky groups into organoboron compounds and boron complexes, which can show emission in solution . Since the first report on aggregation‐induced emission (AIE) was published, AIE‐active molecules have attracted attention not only for preparing bright solid‐state luminescent materials but also for developing stimuli‐responsive materials .…”
Section: Introductionmentioning
confidence: 99%